2016
DOI: 10.1111/chd.12406
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenting in the growing sheep causes aortic endothelial dysfunction but not hypertension: Clinical implications for coarctation repair

Abstract: Background: Stent implantation is the treatment of choice for adolescents and adults with aortic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In fact, in our cohort CoA-PS patients not only had significant higher age at first repair but also higher BMI values compared to the others, and both factors may contribute to the onset hypertension. In addition, Maschietto et al [1] found in animal models elevated markers of oxidative stress and endothelial damage within the aortic wall proximal to a stent, supposing a higher cardiovascular risk in patients after aortic stenting with premature development of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in our cohort CoA-PS patients not only had significant higher age at first repair but also higher BMI values compared to the others, and both factors may contribute to the onset hypertension. In addition, Maschietto et al [1] found in animal models elevated markers of oxidative stress and endothelial damage within the aortic wall proximal to a stent, supposing a higher cardiovascular risk in patients after aortic stenting with premature development of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Coarctation of the aorta (CoA) is the sixth most common cardiovascular malformation, accounting for 5-8% of all congenital heart diseases, and is mostly diagnosed during infancy [1][2][3]. Since the first surgery performed in 1944 by Crawford [4], surgical repair has been the standard of care for isolated CoA for more than 50 years, via an evolution of approaches following the excision of the aortic coarcted segment, including subclavian flap repair, patch augmentation and, the most common used technique, the end-to-end anastomosis [5].…”
Section: Introductionmentioning
confidence: 99%